The Effect of Teachers\' Narrative Therapy on Verbal Intelligence, Creativity, and Lexical Literature of Isfahan Kindergarten Children, Iran - Moluk Tahmasebi; Seyad Ahmad Ahmadi (تحقیقات نظام سلامت, 2022)
Background: Some children have difficulty with verbal intelligence as well as creativity and lexical literature, and as a result, skills such as reading and writing. Using appropriate methods for children, such as narrative therapy, can probably help improve children's learning and academic achievement in the future. The present research was conducted to determine the effect of narrative therapy on verbal intelligence, creativity, and lexical literature in children of Tohid Kindergarten in Isfahan, Iran. Methods: This was an experimental pretest-posttest study with control group. For this purpose, from all children of Tohid Kindergarten in Isfahan City in 2018-2019, 30 children were selected through convenience sampling and randomly assigned into two experimental (n = 15) and control (n = 15) groups. Then the experimental group was trained in 8 sessions of 4 minutes. Before and after the implementation of the independent variable, Wechsler Intelligence Scale for Children (WISC) (verbal understanding and lexical range) and the Torrance Tests of Creative Thinking (TTCT) (form B) were used as research tools. Data were analyzed using analysis of covariance (ANCOVA). Findings: In the pre-test, the mean of verbal intelligence, lexical literature, and creativity in the experimental group was 101, 10.7, 58.7, respectively. And in the post-test phase of the experimental group, these values were obtained 104, 11.5, 65.6, respectively, which indicates an increase in variables in the post-test stage compared to the pre-test. In addition, in the pre-test of the control group, mean of verbal intelligence, lexical literature, and creativity was reported as 99.3, 10.4, and 59, respectively, and in the post-test stage, these values were obtained 99, 10.05, and 58.6, respectively, which indicates that the values of variables in the control group did not differ in pre-test and post-test. Therefore, storytelling training had a significant effect on verbal intelligence (F = 12.88, P < 0.001), lexical literature (F = 14.6, P < 0.001), and creativity (F = 108.48, P < 0.001) variables. Conclusion: Some students have problems in the field of verbal skills and on the other hand, verbal skills are a kind of crystallized intelligence. The results showed that using the method of storytelling had a significant effect on children's verbal intelligence, lexical literature, and creativity in the experimental group compared to control group.